2022
DOI: 10.3389/fonc.2022.968351
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic management of microenvironment acidity in glioblastoma

Abstract: Glioblastoma (GBM), similar to most cancers, is dependent on fermentation metabolism for the synthesis of biomass and energy (ATP) regardless of the cellular or genetic heterogeneity seen within the tumor. The transition from respiration to fermentation arises from the documented defects in the number, the structure, and the function of mitochondria and mitochondrial-associated membranes in GBM tissue. Glucose and glutamine are the major fermentable fuels that drive GBM growth. The major waste products of GBM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 195 publications
1
13
0
Order By: Relevance
“…Succinic acid is a crucial metabolic intermediate involved in a variety of metabolic pathways, which are closely related to tumorigenesis. Previous studies have demonstrated the accumulation of succinic acid in malignancies such as pituitary adenomas (31), ovarian cancers (32), and glioblastomas (33). However, the results of metabolomics showed that the proportion of succinic acid decreased in the PCNSL patient group.…”
Section: Discussionmentioning
confidence: 89%
“…Succinic acid is a crucial metabolic intermediate involved in a variety of metabolic pathways, which are closely related to tumorigenesis. Previous studies have demonstrated the accumulation of succinic acid in malignancies such as pituitary adenomas (31), ovarian cancers (32), and glioblastomas (33). However, the results of metabolomics showed that the proportion of succinic acid decreased in the PCNSL patient group.…”
Section: Discussionmentioning
confidence: 89%
“…73 Acidication of the tumor prompts signicantly higher levels of immunosuppression and GSC migration and proliferation. [74][75][76] Molecular building blocks such as amino acids and nucleosides also have increased concentrations within the TME, contributing to greater aggression, invasion, and immunosuppression. Adenosine, a potent immunosuppressant produced in large quantities in hypoxic conditions by GBM cells and exported into the extracellular space, increases cancer aggressiveness and dampens the immune response through A2A receptors (A2AR) on immune cells.…”
Section: Vascular Changes and Hypoxia In The Tmementioning
confidence: 99%
“…73 Acidification of the tumor prompts significantly higher levels of immunosuppression and GSC migration and proliferation. 74–76…”
Section: The Glioblastoma Microenvironmentmentioning
confidence: 99%
“…Malignant glioma is often diagnosed in older patients but can occur at any age with rising cases in children (Phillips et al, 2006; Tamimi and Juweid, 2017). Median survival is between 8-15 months with overall survival after 5 years remains below 10% (Omuro and DeAngelis, 2013; Fatehi et al, 2018; Seyfried et al, 2022). Patient outcome remains poor due in large part to the invasive characteristics in gliomas making complete surgical resection difficult (McCutcheon and Preul, 2021; Seyfried et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Median survival is between 8-15 months with overall survival after 5 years remains below 10% (Omuro and DeAngelis, 2013; Fatehi et al, 2018; Seyfried et al, 2022). Patient outcome remains poor due in large part to the invasive characteristics in gliomas making complete surgical resection difficult (McCutcheon and Preul, 2021; Seyfried et al, 2022). Gliomas encompass numerous cell types that express glial, stem cell, and mesenchymal markers (Aum et al, 2014; Sidaway, 2017).…”
Section: Introductionmentioning
confidence: 99%